The Response of Macrophages and Neutrophils to Hypoxia in the Context of Cancer and Other Inflammatory Diseases - Antje Egners; Merve Erdem; Thorsten Cramer (Mediators of Inflammation)
Lack of oxygen (hypoxia) is a hallmark of a multitude of acute and chronic diseases and can be either beneficial or detrimental for organ restitution and recovery. In the context of inflammation, hypoxia is particularly important and can significantly influence the course of inflammatory diseases. Macrophages and neutrophils, the chief cellular components of innate immunity, display distinct properties when exposed to hypoxic conditions. Virtually every aspect of macrophage and neutrophil function is affected by hypoxia, amongst others, morphology, migration, chemotaxis, adherence to endothelial cells, bacterial killing, differentiation/polarization, and protumorigenic activity. Prominent arenas of macrophage and neutrophil function, for example, acute/chronic inflammation and the microenvironment of solid tumors, are characterized by low oxygen levels, demonstrating the paramount importance of the hypoxic response for proper function of these cells. Members of the hypoxia-inducible transcription factor (HIF) family emerged as pivotal molecular regulators of macrophages and neutrophils. In this review, we will summarize the molecular responses of macrophages and neutrophils to hypoxia in the context of cancer and other chronic inflammatory diseases and discuss the potential avenues for therapeutic intervention that arise from this knowledge.